SETD2 epidermal deficiency promotes cutaneous wound healing via activation of AKT/mTOR Signalling. (5th May 2021) - Li, Xiaoxue; Liu, Changwei; Zhu, Yiwen; Rao, Hanyu; Liu, Min; Gui, Liming; Feng, Wenxin; Tang, Huayuan; Xu, Jin; Gao, Wei‐Qiang; Li, Li
Abstract: Objectives: Cutaneous wound healing is one of the major medical problems worldwide. Epigenetic modifiers have been identified as important players in skin development, homeostasis and wound repair. SET domain–containing 2 (SETD2) is the only known histone H3K36 tri‐methylase; however, its role in skin wound healing remains unclear. Materials and Methods: To elucidate the biological role of SETD2 in wound healing, conditional gene targeting was used to generate epidermis‐specific Setd2 ‐deficient mice. Wound‐healing experiments were performed on the backs of mice, and injured skin tissues were collected and analysed by haematoxylin and eosin (H&E) and immunohistochemical staining. In vitro, CCK8 and scratch wound‐healing assays were performed on Setd2 ‐knockdown and Setd2 ‐overexpression human immortalized keratinocyte cell line (HaCaT). In addition, RNA‐seq and H3K36me3 ChIP‐seq analyses were performed to identify the dysregulated genes modulated by SETD2. Finally, the results were validated in functional rescue experiments using AKT and mTOR inhibitors (MK2206 and rapamycin). Results: Epidermis‐specific Setd2 ‐deficient mice were successfully established, and SETD2 deficiency resulted in accelerated re‐epithelialization during cutaneous wound healing by promoting keratinocyte proliferation and migration. Furthermore, the loss of SETD2 enhanced the scratch closure and proliferation of keratinocytes in vitro. Mechanistically, the deletion of Setd2 resulted in the activation of AKT/mTOR signalling pathway, while the pharmacological inhibition of AKT and mTOR with MK2206 and rapamycin, respectively, delayed wound closure. Conclusions: Our results showed that SETD2 loss promoted cutaneous wound healing via the activation of AKT/mTOR signalling. Abstract : The epidermis‐specific Setd2 ‐deficient mice showed accelerated re‐epithelialization during cutaneous wound healing by promoting keratinocytes proliferation and migration. Mechanistically, deletion of Setd2 resulted in the activation the AKT/mTOR signalling pathway and pharmacological inhibitions of AKT and mTOR with MK2206 and rapamycin delayed wound closure, respectively.